Contextualising Health Agency : Exploration of Narratives from Marginalised Women in Varanasi, India - Sinha, Shalvi (2024)
Gender equality and women’s empowerment are critical development goals which are highlighted by global agendas such as the Beijing Declaration and Platform for Action and the Sustainable Development Goals. A key facet of these attempts is understanding and expanding women’s agency, particularly to advance their health. However, traditional metrics often impose ideals of agency from a western standpoint and struggle to define and measure agency within women’s contexts.